Core stability in athletes: A critical analysis of current guidelines - Wirth, K.; Hartmann, H.; Mickel, C.; Szilvas, E.; Keiner, M.; Sander, A. (Sports Medicine, 2017)
Over the last two decades, exercise of the core muscles has gained major interest in professional sports. Research has focused on injury prevention and increasing athletic performance. We analyzed the guidelines for so-called functional strength training for back pain prevention and found that programs were similar to those for back pain rehabilitation; even the arguments were identical. Surprisingly, most exercise specifications have neither been tested for their effectiveness nor compared with the load specifications normally used for strength training. Analysis of the scientific literature on core stability exercises shows that adaptations in the central nervous system (voluntary activation of trunk muscles) have been used to justify exercise guidelines. Adaptations of morphological structures, important for the stability of the trunk and therefore the athlete`s health, have not been adequately addressed in experimental studies or in reviews. In this article, we explain why the guidelines created for back pain rehabilitation are insufficient for strength training in professional athletes. We critically analyze common concepts such as `selective activation` and training on unstable surfaces.